APPLICATION OF THE MULTIPLE REPRESENTATION LEARNING MODEL TO IMPROVE STUDENTS' SCIENTIFIC LITERACY ABILITIES AT SMP NEGERI 13 MAKASSAR - Sarina, Sarina; Dewanto, Riski; Pertiwi, Andini; Assagaf, Muhammad Dzulfikar (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
This study aims to determine: 1) the extent of improvement in science literacy skills among eighth-grade students at SMP Negeri 13 Makassar after implementing the multiple representation learning model, and 2) whether there is a significant difference in the average score improvement in science literacy skills among eighth-grade students at SMP Negeri 13 Makassar before and after the implementation of the multiple representation learning model. This research employs a pre-experimental design using the One Group Pretest-Posttest Design. The study population includes all eighth-grade students at SMP Negeri 13 Makassar, with purposive sampling selecting class VIII B as the sample. The research instrument used is a science literacy test. Data were analyzed using descriptive and inferential statistics. The analysis results indicate that: 1) there is an improvement in science literacy skills among eighth-grade students at SMP Negeri 13 Makassar taught using the multiple representation learning model, which falls into the moderate category, and 2) there is a significant difference in the average score improvement in science literacy skills among students before and after the implementation of the multiple representation learning model.